1988
DOI: 10.1007/bf00130000
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolating global visual field indices from local parameters in the nasal region

Abstract: The local mean and the average difference of four pairs of test locations within the 26 degrees visual field, situated above and below the horizontal nasal meridian, were used to predict the global field indices MD and CLV of the Gl glaucoma program. Out of 539 examinations (194 eyes suspected of having glaucoma), the local indices NDIFF (describing asymmetrical behavior around the nasal horizontal meridian), ND0 (the mean defect in the nasal region), and the global indices MD and CLV were calculated. Seven hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Automated perimetry has become an accepted standard of practice, allowing physicians to monitor the development of glaucomatous visual field loss. Very few longitudinal studies of any size and magnitude 12,[26][27][28][29][30][31][32][33][34][35] involving the classification of abnormal glaucomatous visual fields have been conducted. Previous investigators have developed classification systems to identify the pattern and severity of glaucomatous visual field loss.…”
Section: Commentmentioning
confidence: 99%
“…Automated perimetry has become an accepted standard of practice, allowing physicians to monitor the development of glaucomatous visual field loss. Very few longitudinal studies of any size and magnitude 12,[26][27][28][29][30][31][32][33][34][35] involving the classification of abnormal glaucomatous visual fields have been conducted. Previous investigators have developed classification systems to identify the pattern and severity of glaucomatous visual field loss.…”
Section: Commentmentioning
confidence: 99%
“…A number of studies have reported surprisingly high sensitivities and specificities with few test locations only [3,5,12,13,17,22,24,25]. However, their authors have all selected the best test locations retrospectively.…”
Section: Discussionmentioning
confidence: 96%